2005
DOI: 10.1038/sj.sc.3101781
|View full text |Cite
|
Sign up to set email alerts
|

Upper thoracic disc herniation followed by acutely progressing paraplegia

Abstract: Study design: Case report. Objective: To report a rare thoracic intervertebral disc herniation followed by acutely progressing paraplegia. Setting: Spinal Injuries Center, Fukuoka, Japan. Method: A 37-year-old man presented with sudden severe backache and acutely progressing motor impairments of both lower extremities after antecedent backache lasting about 5 days. Neurological examination showed analgesia and hypoesthesia below the T4 dermatome level, dysesthesia to pinprick below right inguinal level, and se… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

3
10
0

Year Published

2010
2010
2024
2024

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(13 citation statements)
references
References 13 publications
3
10
0
Order By: Relevance
“…When analyzing our personal series and case reports in the literature, 6,12,14,15,17,24,28 it seems that TDHs presenting with an acute myelopathy share some particular radiological and clinical features.…”
Section: Particular Features Of Tdhs Presenting With Acute Myelopathymentioning
confidence: 97%
See 2 more Smart Citations
“…When analyzing our personal series and case reports in the literature, 6,12,14,15,17,24,28 it seems that TDHs presenting with an acute myelopathy share some particular radiological and clinical features.…”
Section: Particular Features Of Tdhs Presenting With Acute Myelopathymentioning
confidence: 97%
“…Although some authors have stated that TDHs more frequently cause an acute paraplegia than their cervical counterparts, 12,25 there are actually few case reports concerning this entity. 5,6,12,14,15,17,24,28 Interestingly, we have treated 8 patients affected by an acute myelopathy (including 3 with paraplegia, 2 with severe paraparesis, and 1 with severe monoparesis) at our institution over the past 8 years. When confronted with such a patient, the surgeon has to decide whether to perform an emergency operation and if so, whether to use an anterior or posterior approach, considering the anticipated risk of such an attempt.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…However, the symptoms usually progress slowly when it does occur [9]. Sasaki et al [10] was the first to describe upper thoracic disc herniation followed by acutely progressing paraplegia, and several authors have reported that thoracic disc herniation is usually associated with radiological disc calcification [11-13]. However, in our case, the CT scans and gross examination of the excised herniated disc failed to provide any evidence of calcification.…”
Section: Discussionmentioning
confidence: 74%
“…However, in our case, the CT scans and gross examination of the excised herniated disc failed to provide any evidence of calcification. Two reports have described cases of thoracic disc herniation sequestrated to the posterior side of the spinal canal that resulted in paraplegia [10,14]. In these cases, the thoracolumbar radiographs and CT also showed no herniated disc calcification.…”
Section: Discussionmentioning
confidence: 99%